Achog1 is required for the asexual sporulation, stress responses and pigmentation of Aspergillus cristatus - Shao, Lei; Tan, Yumei; Song, Shiying; Wang, Yuchen; Liu, Yongxiang; Huang, Yonghui; Ren, Xiyi; Liu, Zuoyi (Frontiers in Microbiology, 2022)
Aspergillus cristatus is the dominant fungus during the fermentation of Fuzhuan brick tea; hypotonic conditions only induce its sexual development to produce ascospores, while hypertonic conditions only induce its asexual development to produce conidia, indicating that osmotic stress can regulate spore production in A. cristatus. However, the underlying regulatory mechanism is unclear. In this study, the role of Achog1, which is homologous to hog1 from Saccharomyces cerevisiae, in sporulation, different kinds of stress responses and pigment production was investigated. Deletion mutants of Achog1 were obtained by homologous recombination. Phenotypic observations showed that the time required to produce conidia was delayed, and the number of conidia produced was significantly reduced in the deletion mutants of Achog1 in hypertonic media, indicating that Achog1 plays a positive role in asexual development. Stress sensitivity tests showed that ΔAchog1 strains were sensitive to hyperosmolarity, and the order of the sensitivity of ΔAchog1 to different osmotic regulators was 3 M sucrose > 3 M NaCl > 3 M sorbitol. Moreover, the deletion mutants were sensitive to high oxidative stress. pH sensitivity tests indicated that Achog1 inhibited the growth of A. cristatus under alkaline stress. Additionally, pigmentation was decreased in the Achog1 deletion mutants compared with the WT. All the above developmental defects were reversed by the reintroduction of the Achog1 gene in ΔAchog1. Pull-down and LC–MS/MS analysis showed that the expression levels of proteins interacting with Achog1 were significantly different under low and high osmotic stress, and proteins related to conidial development were present only in the cultures treated with hyperosmotic stress. Transcription profiling data showed that Achog1 suppressed the expression of several genes related to asexual development, osmotic stress resistance and oxidative stress resistance. On the basis of gene knockout, pull-down mass spectrometry and RNA-seq analyses, a regulatory pathway for Achog1 was roughly identified in A. cristatus.